Cost and greenhouse gas emissions of current, healthy, flexitarian and vegan diets in Aotearoa (New Zealand). Issue 1 (9th June 2021) - Kidd, Bruce; Mackay, Sally; Vandevijvere, Stefanie; Swinburn, Boyd
Abstract : Objective: To compare the costs and climate impact (greenhouse gas emissions) associated with current and healthy diets and two healthy and environmentally friendly dietary patterns: flexitarian and vegan. Design: Modelling study Setting: Aotearoa (New Zealand). Main outcome measures: The distribution of the cost and climate impact (kgCO2 e/kg of food per fortnight) of 2 weekly current, healthy, vegan and flexitarian household diets was modelled using a list of commonly consumed foods, a set of quantity/serves constraints for each, and constraints for food group and nutrient intakes based on dietary guidelines (Eating and Activity Guidelines for healthy diets and EAT-Lancet reference diet for vegan and flexitarian diets) or nutrition survey data (current diets). Results: The iterative creation of 210–237 household dietary intakes for each dietary scenario was achieved using computer software adapted for the purpose (DIETCOST). There were stepwise differences between diet scenarios (p<0.001) with the current diet having the lowest mean cost in New Zealand Dollars (NZ584 (95% CI NZ580 to NZ588)) per fortnight for a family of four) but highest mean climate impact (597 kgCO2 e (95% CI 590 to 604 kgCO2 e)), followed by the healthy diet (NZ637 (95% CI NZ632 to NZ642), 452 kgCO2 e (95% CI 446 to 458 kgCO2 e)), the flexitarian diet (NZ728 (95% CI NZ723 to NZ734), 263 kgCO2 e (95% CI 261 to 265 kgCO2 e)) and the vegan diet, which had the highest mean cost and lowest mean climate impact (NZ789, (95% CI NZ784 to NZ794), 203 kgCO2 e (95% CI 201 to 204 kgCO2 e)). There was a negative relationship between cost and climate impact across diets and a positive relationship within diets. Conclusions: Moving from current diets towards sustainable healthy diets (SHDs) will reduce climate impact but generally at a higher cost to households. The results reflect trade-offs, with the larger constraints placed on diets, the greater cost and factors such as nutritional adequacy, variety, cost and low-emissions foods being considered. Further monitoring and policies are needed to support population transitions that are country specific from current diets to SHD.